ANALYSIS OF THE INFLUENCE OF THE EXPOSURE CAREER FUNCTION OF MENTORSHIP ON WOMEN’S LEADERSHIP ADVANCEMENT IN KENYAN UNIVERSITIES - Severina, Wambeti Njagi; Edabu, Dr. Paul; Kimani, Dr. Cecilia (IJRDO- Journal of Educational Research, 2016)
Women working in Kenyan universities should be provided with the many benefits of exposurewhich is a mentorship function. They shoukd for example get support in networking. Thishowever may not be taking place in these universities. Therefore, the researcher did this studyfor the purpose of determining the influence of exposure on women’s leadership advancement inKenyan universities. A mixed methodology, using a triangulation design-convergence model wasapplied to realize the objective. The findings were that the women have limited exposure, thustheir chances of leadership advancement are hindered. The conclusion was that women workingin Kenyan universities should get enough exposure so that their chances of leadershipadvancement can be enhanced. Data analysis for example demonstrated that in Kenyanuniversities, mentors rarely give mentees opportunities to demonstrate their knowledge andnetwork extensively. Women in universities should be fully exposed so as to meet importantpeople who can help them advance.